2012
DOI: 10.1111/j.1440-6055.2012.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew as a source of nutrition for Lysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae): effect of adult diet on lifespan and egg load

Abstract: Parasitoid survival and fecundity is generally enhanced with access to carbohydrate food sources. In many agricultural ecosystems, there is often a scarcity of suitable carbohydrates for parasitoids. This study compared the suitability of aphid honeydew and buckwheat nectar as diet for the aphid parasitoid Lysiphlebus testaceipes. Wasp lifespan and egg load were both increased with access to carbohydrates, but no differences were detected between the various carbohydrates diets tested. As aphid honeydew is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Out of the seven species tested, flowers of F. esculentum and L. maritima were the ones that most benefit the survival of both males and females of the three T. absoluta parasitoids. Survival increases associated with F. esculentum and L. maritima obtained in this work agree with those obtained by Balzan and Wäckers (2013) for N. artynes and with similar studies done with other braconid species (Berndt and Wratten, 2005;Hopkinson et al 2013;Johanowicz and Mitchell, 2000;Nafziger Jr. and Fadamiro, 2011;Vattala et al 2006;Winkler et al 2009a).…”
Section: Discussionsupporting
confidence: 91%
“…Out of the seven species tested, flowers of F. esculentum and L. maritima were the ones that most benefit the survival of both males and females of the three T. absoluta parasitoids. Survival increases associated with F. esculentum and L. maritima obtained in this work agree with those obtained by Balzan and Wäckers (2013) for N. artynes and with similar studies done with other braconid species (Berndt and Wratten, 2005;Hopkinson et al 2013;Johanowicz and Mitchell, 2000;Nafziger Jr. and Fadamiro, 2011;Vattala et al 2006;Winkler et al 2009a).…”
Section: Discussionsupporting
confidence: 91%
“…Typically, parasitoid egg load depends on the diet provided to adult females, as reported for the parasitoid P. cerealellae (Onagbola et al 2007). Honey is usually the most effective sugar source to promote egg maturation (Hogervorst et al 2007a;Hopkinson et al 2013), and when it is replaced with sugar-poor diets, ovaries of gravid F. arisanus females show deterioration, by decreasing egg load from over 100 eggs to less than 70 immediately before their death (Bautista et al 2001). The maximum egg load of the ichneumonid parasitoid B. curculionis greater benefits from honey (+15%) than from honeydew excreted by the pea aphid, Acyrthosiphon pisum (Harris) (England and Evans 1997).…”
Section: Egg Load Maturation and Resorptionmentioning
confidence: 99%
“…This may be attributed to parasitoids having access to honeydew excreted by P. ficus. Mealybug and aphid honeydew can be a significant source of food for some parasitoids (Sandanayaka et al 2009;Hopkinson et al 2013), but not always (Davies et al 2004). Suma et al (2012) demonstrated that exposure to hosts and honeydew enhanced longevity of A. sp.…”
Section: Discussionmentioning
confidence: 99%